Forty years of European Society for Muscle Research - Marcus C. Schaub (PAGEPress Publications, 2010)
The European Muscle Club was founded 1971 and since 1972 yearly muscle conferences were held in turn in different European countries. Regular scientific meetings in the field of muscle research did not exist before. The name of the Muscle Club was 1988 changed to European Society for Muscle Research (ESMR). The yearly meetings usually attract 200-300 participants. The 39th meeting will be held 11-15 Sept. 2010 in Abano Terme near Padova, and the 40th meeting 14-18 Sept. 2011 in Berlin. Since 1980 the meeting reports and abstracts are regularly published in the Journal of Muscle Research and Cell Motility (JMRCM). The history of the society and the muscle scientists involved with it will be outlined.